2002
DOI: 10.1021/ie020565z
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Catalyzed Reactions in Carbon Dioxide-Enriched High-Temperature Liquid Water

Abstract: We report, for the first time, the acceleration of acid-catalyzed reactions in high-temperature liquid water by the addition of carbon dioxide to the reaction medium. The reactions examined are the dehydration of cyclohexanol to form cyclohexene and the alkylation of p-cresol with tertbutyl alcohol to form 2-tert-butyl-4-methylphenol. In some cases, the mean product yield more than doubled when carbon dioxide was added to the aqueous medium. The basis of this rate enhancement is reaction between carbon dioxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
72
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 18 publications
1
72
0
1
Order By: Relevance
“…Table 1 shows that the amount of Pd on the Pd particles and weakens π back-donation from Pd to adsorbate species, which prevents the phenol from adsorption and reaction. The rapid catalyst deactivation observed in the presence of both CO 2 and water may be ascribed to the acidic nature of the aqueous phase [29][30][31]. This causes the leaching of Pd in a larger amount and a more significant structural change in the surface of Pd particles.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Table 1 shows that the amount of Pd on the Pd particles and weakens π back-donation from Pd to adsorbate species, which prevents the phenol from adsorption and reaction. The rapid catalyst deactivation observed in the presence of both CO 2 and water may be ascribed to the acidic nature of the aqueous phase [29][30][31]. This causes the leaching of Pd in a larger amount and a more significant structural change in the surface of Pd particles.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Recently, Hunter and Savage reported, for the first time, the acceleration of simple acid-catalyzed organic reactions in high-temperature liquid water by adding carbon dioxide; carbonic acid generated in situ from water and carbon dioxide lowers the pH of the solution (20). The addition of carbon dioxide as an environmentally benign acid catalyst also should be effective for polysaccharide hydrolyses under hydrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%
“…[75][76][77][78][79][80][81][82] Notably, the formation of carbonic acid can enhance the rate of acid-catalyzed reactions, which include hydrolysis and dehydration, without the drawback of neutralization and/or solvent recovery. 75,76,[82][83][84][85][86] The use of CO 2 -H 2 O mixtures during biomass pre-treatment has also been shown to reduce the crystallinity of the cellulose-rich fraction allowing a reduction in enzyme loading of 33% during subsequent saccharification. 86 Relvas et al modelled the kinetics of the hemicellulose, xylan and arabinan hydrolysis in the presence of CO 2 added during hydrothermal processes and demonstrated that the formation of carbonic acid led to an increase in the kinetic reaction constants for both intermediates and final products.…”
Section: Catalytic Processesmentioning
confidence: 99%